Strategy For Repackaging Information On Instagram Social Media (Case Study: Bookstagrammer Indonesia) - Ummi Afzah Amirah; Franindya Purwaningtyas (SEAN Institute, 2024)
This study aims to determine the strategy of Indonesian bookstagrammers in packaging information that is interesting and informative for their audience , the format or content used in packaging information , the impact of bookstagrammer accounts on their audience , and how bookstagrammers can build a strong identity and community through this information packaging strategy . In this research process , the author uses a qualitative research method with a case study research type . The data collection method is carried out using the triangulation method by combining observation , FGD ( Focus Group Discussion ) and documentation . Furthermore , the stages in analyzing data using the Miles and Huberman model which functions of 3 main things : Data Reduction ( simplification ), Data Presentation , and finally Conclusion Drawing / Verification . The results showed that bookstagrammers apply the five hierarchies of design needs , namely the levels of functionality , reliability , usability , profession and creativity . The information packaging strategy activities carried out by bookstagrammers aim to disseminate information related to books , reading places. places that are reviewed in the selected content format to shows their characteristics or characteristics as bookstagrammers . Bookstagrammer becomes a reference and motivation for followers to read books , buy books through its repackaged content . In this case , bookstagrammers also build communications both with Instagram followers , with other bookstagrammers .